The Effect of Wordwall-Based Quizzes on Students’ Science Learning Outcomes at Elementary School 78 Palembang - Arsita, Monica; Hetilaniar, Hetilaniar; Sri Nindiati, Dina (SEMESTA: Journal of Science Education and Teaching, 2025)
This study investigated the effect of Wordwall quiz-based media on fifth-grade students’ science learning outcomes at SD Negeri 78 Palembang. This quantitative research employed a quasi-experimental design, specifically a posttest-only control group design. The population consisted of all fifth-grade students, comprising five classes with a total of 112 students. The research sample was selected using a random sampling technique, resulting in class V.D as the experimental group and class V.A as the control group. Data were collected through tests and documentation. The research was conducted on Theme 7, Events in Life, under Subtheme 1, National Events During the Colonial Period. The data were analyzed using an independent sample t-test, which yielded a tcount of 5.075 ≥ ttable value of 2.01954 and a significance value (2-tailed) of 0.000 < 0.05. Therefore, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. These results indicate that the use of Wordwall quiz-based media significantly improves students’ science learning outcomes at SD Negeri 78 Palembang.